(untitled) (Zaranie Śląskie, 2025)
Racibórz, as a so-called “trophy city”, located within the borders of the Third Reich, was treated by the Soviets with exceptional brutality. First came the organized looting of property, both industrial and private, followed by deliberate arson of the city’s central buildings. The ruined Silesian city was handed over to the Polish authorities only after more than two months under the rule of a Soviet commandant. Deprived of its pre-war fabric of society, Racibórz faced the necessity of rebuilding its demographic potential. Thousands of residents, who had fled westward from December 1944 ahead of the front lines, decided to remain in Germany, settling mostly in the regions of Roth and Leverkusen. Those who returned, realizing the new political realities, either chose to emigrate again or were forcibly expelled. The repopulation of the city took place under entirely new circumstances. The social landscape, previously dominated by the German population, was replaced by a new fabric woven from post-war destinies and traumas. Alongside the native Silesian population, many of whom were widows and orphans and often spoke Polish, the city became home to Poles resettled from the Eastern Borderlands. They came mainly from Sambor, Stanisławów, Chodorów, and Łuck, as well as from other regions of pre-war Poland. Among them there were soldiers of the Home Army, including participants of the Warsaw Uprising, and members of other underground resistance formations. The so-called “Recovered Territories” were seen as a safe haven. Reconstruction began paradoxically with destruction — by demolishing German tenement houses. The building materials were shipped to Warsaw. The authorities noticed with concern the growing closeness between Silesians and settlers from the East, so they built the foundations of the militia and secret political police on battle-tested soldiers of the Polish Army who had fought alongside the Red Army or on members of the communist resistance movement. Adding to the tension was the Polish–Czechoslovak border dispute over Racibórz, Kłodzko, and Głubczyce. The fate of Racibórz, once the Upper Silesian capital, unfolded quite differently from that of Upper Silesian cities incorporated into the reborn Second Polish Republic after 1921 — and the consequences of this are still visible today.